2003
DOI: 10.1038/sj.onc.1206644
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 complexes containing cJun and JunB cause cellular transformation of Rat1a fibroblasts and share transcriptional targets

Abstract: To investigate the role of individual Jun proteins in cell growth and transformation, we have used a doxycyclineinducible retroviral vector to regulate their expression in rat fibroblasts. AP-1 complexes enriched with cJun and JunB result in morphological alterations and anchorageindependent cell growth consistent with a transformationlike phenotype, whereas complexes enriched with JunD had an antiproliferative effect. These results suggest that genes regulated by both cJun and JunB are potentially involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 50 publications
5
42
0
1
Order By: Relevance
“…Although, c-Jun and JunB may induce opposite effects (43), they also have gene targets in common (44). Interestingly, JunB has been suggested to substitute c-Jun during mouse development and cell proliferation when c-Jun is depleted (45), further supporting our suggestion that AP-1 family members take their promoter-specific interaction with TAF4b into their own hands and follow with regulation of transcription.…”
Section: Ap-1 Family Members Share Transcriptional Regulation Of Targsupporting
confidence: 66%
“…Although, c-Jun and JunB may induce opposite effects (43), they also have gene targets in common (44). Interestingly, JunB has been suggested to substitute c-Jun during mouse development and cell proliferation when c-Jun is depleted (45), further supporting our suggestion that AP-1 family members take their promoter-specific interaction with TAF4b into their own hands and follow with regulation of transcription.…”
Section: Ap-1 Family Members Share Transcriptional Regulation Of Targsupporting
confidence: 66%
“…Although the role of c-Jun in human cancers remains to be defined, substantial evidence suggests that it is involved in cellular proliferation and transformation. Deregulated expression of c-Jun induces immortalised rat fibroblasts to grow in an anchorage-independent fashion (SchĂŒtte et al, 1989) depending on the induction of multiple c-Jun target genes Leaner et al, 2003Leaner et al, , 2005Hommura et al, 2004;Katabami et al, 2005). Recent studies reported that specific AP-1 blockade by a dominantnegative mutant of c-Jun, TAM67, inhibited the growth of some types of human cancer cells by causing G1 arrest (Ludes-Meyers et al, 2001;Liu et al, 2004;Suto et al, 2004).…”
mentioning
confidence: 99%
“…As c-Jun/AP-1 can additionally regulate many other genes participating in different steps of transformation (Refs. 7,14,20,32,33,51, and this study), it could offer a good target for cancer therapeutic trials. However, as we did not find TAM67 to fully inhibit the expression of the three invasion/metastasis-regulating molecules, it is possible that some kind of combination therapy, consisting of a cocktail of inhibitors for integrins, cysteine cathepsins, and thymosin b4, could result in a more effective therapeutic (anti-metastatic) response in the aggressive human/animal fibrosarcomas and other sarcomas/ tumors overexpressing these molecules.…”
Section: Discussionmentioning
confidence: 99%